A Coplanar π‐Extended Quinoxaline Based Hole‐Transporting Material Enabling over 21 % Efficiency for Dopant‐Free Perovskite Solar Cells. Issue 5 (30th November 2020) - Guo, Huanxin; Zhang, Hao; Shen, Chao; Zhang, Diwei; Liu, Shuaijun; Wu, Yongzhen; Zhu, Wei‐Hong
Abstract: Developing dopant‐free hole transporting materials (HTMs) is of vital importance for addressing the notorious stability issue of perovskite solar cells (PSCs). However, efficient dopant‐free HTMs are scarce. Herein, we improve the performance of dopant‐free HTMs featuring with a quinoxaline core via rational π‐extension. Upon incorporating rotatable or chemically fixed thienyl substitutes on the pyrazine ring, the resulting molecular HTMs TQ3 and TQ4 show completely different molecular arrangement as well as charge transporting capabilities. Comparing with TQ3, the coplanar π‐extended quinoxaline based TQ4 endows enriched intermolecular interactions and stronger π–π stacking, thus achieving a higher hole mobility of 2.08×10 −4 cm 2 V −1 s −1 . It also shows matched energy levels and high thermal stability for application in PSCs. Planar n‐i‐p structured PSCs employing dopant‐free TQ4 as HTM exhibits power conversion efficiency (PCE) over 21 % with excellent long‐term stability. Abstract : Quinoxaline derivatives, featuring with rotatable and chemically fixed thienyl substitutes, are introduced as the core for constructing dopant‐free hole transporting materials (HTMs). The coplanar π‐extended quinoxaline‐based HTM TQ4 achieves the best photovoltaic performance (exceed 21 %) among planar n‐i‐p structured dopant‐free perovskite solar cells.